2019
DOI: 10.3389/fneur.2019.01091
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Assessing Non-severe Elevation of Intracranial Pressure Using Optic Nerve Sheath Diameter and Transcranial Doppler Parameters

Abstract: Background/Aims: Non-invasive measurement of intracranial pressure (ICP) using ultrasound has garnered increasing attention. This study aimed to compare the reliability of ultrasonographic measurement of optic nerve sheath diameter (ONSD) and transcranial Doppler (TCD) in detecting potential ICP elevations.Methods: Patients who needed lumbar puncture (LP) in the Department of Neurology were recruited from December 2016 to July 2017. The ONSD and TCD measurements were completed before LP.Results: One hundred si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The MCA-PI derived by transcranial Doppler ultrasonography is reportedly correlated with the ICP and cerebral perfusion pressure in various intracranial disorders, such as traumatic brain injury, intracranial hemorrhage, subarachnoid hemorrhage, and hypoxic brain injury after cardiac arrest. 9,10,1417 In the present study, the increased MCA-PI in patients with intracranial lesions might reflect an increased ICP secondary to a hematoma or cerebral edema. In addition, increased peripheral vascular resistance because of ischemic stroke might have also contributed.…”
Section: Discussionmentioning
confidence: 52%
“…The MCA-PI derived by transcranial Doppler ultrasonography is reportedly correlated with the ICP and cerebral perfusion pressure in various intracranial disorders, such as traumatic brain injury, intracranial hemorrhage, subarachnoid hemorrhage, and hypoxic brain injury after cardiac arrest. 9,10,1417 In the present study, the increased MCA-PI in patients with intracranial lesions might reflect an increased ICP secondary to a hematoma or cerebral edema. In addition, increased peripheral vascular resistance because of ischemic stroke might have also contributed.…”
Section: Discussionmentioning
confidence: 52%
“…Measured 3 times and then averaged. Chen 2019 [ 14 ] China Prospective 29 4.53 DelicaMVU-6300 Mixed LP Mixed 3 mm behind the globe; averaged two measurements: one sagittal and the other in the transverse plane del Saz-Saucedo 2016 [ 15 ] Spain Prospective 19 6.76 Toshiba AplioXG Mixed LP IIH Transverse plane Du 2020 [ 16 ] China Prospective 49 5.7 Sonosite ICU Inv Trauma 3 mm behind the globe; transverse plane; averaged two eyes. Geeraerts 2007 [ 17 ] France Prospective 15 6.3 HP Sonos 5500 ICU Inv Trauma 3 mm behind the globe; one sagittal and one transverse Goel 2008 [ 18 ] India Prospective 73 5.8 Unspecified Mixed CT Trauma 3 mm behind the globe; one sagittal and one transverse; averaged Hanafi 2019 [ 19 ] Iran Prospective 62 ...…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies stipulate that PI is not very reliable for evaluating ICP [22,23] . Chen et al suggested that cerebral arterial hemodynamics assessed by TCD are not a su ciently reliable predictor of ICP in the early IH stages [24] , making its clinical applicability controversial. Whether or not TCD can be used to evaluate neurological disease prognosis has attracted attention.…”
Section: Discussionmentioning
confidence: 99%